A Theological Review of Strategic Human Resource Development Management for Christian Leadership - Purba, Eli Brigita; Vivian, Elvan; Jonathan, Merrick (IAKN TORAJA, 2024)
Abstract: This study analyses Christian leadership development strategies based on Christian values, including: (1) character building, (2) knowledge enhancement, (3) skill development, (4) monitoring and evaluation, and (5) strengthening sustainable regeneration. Development focuses on three pillars: character, knowledge, and skills, which also serve as an evaluation framework. The research uses qualitative methods with data from literature review. Jesus and Moses exemplify ideal Christian leaders, demonstrating the importance of soft and hard skills. Development should be regularly measured and evaluated. Self-development and succession planning should be conducted through structured self-evaluation and consistent feedback from others. In conclusion, Christian leadership development can begin with three pillars: character, knowledge, and skills. This strategy aims to develop leaders holistically. For further research, field studies focusing on church leaders in Indonesia are recommended. Keywords: Christian Leaders, Human Resource Development, Management, Strategy. Abstrak: Studi ini menganalisis strategi pengembangan pemimpin Kristen berbasis nilai-nilai Kristen, meliputi: (1) membangun karakter, (2) meningkatkan pengetahuan, (3) mengasah kompetensi dan keterampilan, (4) monitoring dan evaluasi, serta (5) memperkuat kaderisasi berkelanjutan. Pengembangan berfokus pada tiga pilar: karakter, pengetahuan, dan keterampilan, yang juga digunakan sebagai kerangka evaluasi. Penelitian ini menggunakan metode kualitatif dengan data yang diperoleh melalui tinjauan pustaka. Yesus dan Musa ditampilkan sebagai contoh pemimpin Kristen yang menunjukkan pentingnya soft skills dan hard skills. Pengembangan harus diukur serta dievaluasi secara berkala. Kaderisasi dan pengembangan diri dilakukan melalui evaluasi diri dan umpan balik yang terstruktur dan konsisten. Kesimpulannya, pengembangan pemimpin Kristen dapat dimulai dengan tiga pilar utama: karakter, pengetahuan, dan keterampilan. Strategi ini bertujuan mengembangkan pemimpin secara holistik. Untuk penelitian lebih lanjut, disarankan menggunakan penelitian lapangan dengan objek para pemimpin gereja di Indonesia. Kata Kunci: Manajemen, Pemimpin Kristen, Pengembangan SDM, Strategi